Improvement of the SAG ampacity carrying level of existing 275 KV overhead line tower by using the re-conductoring approach - Baharom, Md Nor Ramdon; Mahmod, Luqman Hakim; Zainal, Zainab; Ullah, Irshad; Ali, Irfan (Asian Research Publishing Network (ARPN), 2015)
Urban cities grown in population day by day, proportionally to the electricity demand. The existence of the right of ways and the decreasing of land space to build new overhead transmission line towers, other criterion had to be observed. Other than upgrading towers, re-conductoring can be pursued if it does not violates the right of ways in any aspect. This project compares available conductors in the market to determine which will provide better performance in terms of current and sag for 275 kV lattice tower.